2017
DOI: 10.1007/s00784-017-2136-9
|View full text |Cite
|
Sign up to set email alerts
|

Immediate definitive individualized abutments reduce peri-implant bone loss: a randomized controlled split-mouth study on 16 patients

Abstract: Non-detached immediate definitive lithium-disilicate individualized abutments and provisionalization through digital technology resulted in successful clinical outcomes and can be routinely applied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 32 publications
0
13
0
2
Order By: Relevance
“…The Pink Aesthetic Score (PES ;Furhauser et al, 2005), which only assesses the soft tissues, was used in two studies (Erhan Comlekoglu et al, 2018;Schepke et al, 2017), demonstrating improvement in these scores after 1 year in one study (Schepke et al, 2017), while in the other the results were opposite, as they reported slight worsening 8 months after loading (Erhan Comlekoglu et al, 2018). The Pink Aesthetic Score (PES ;Furhauser et al, 2005), which only assesses the soft tissues, was used in two studies (Erhan Comlekoglu et al, 2018;Schepke et al, 2017), demonstrating improvement in these scores after 1 year in one study (Schepke et al, 2017), while in the other the results were opposite, as they reported slight worsening 8 months after loading (Erhan Comlekoglu et al, 2018).…”
Section: Aesthetic Indicesmentioning
confidence: 99%
See 2 more Smart Citations
“…The Pink Aesthetic Score (PES ;Furhauser et al, 2005), which only assesses the soft tissues, was used in two studies (Erhan Comlekoglu et al, 2018;Schepke et al, 2017), demonstrating improvement in these scores after 1 year in one study (Schepke et al, 2017), while in the other the results were opposite, as they reported slight worsening 8 months after loading (Erhan Comlekoglu et al, 2018). The Pink Aesthetic Score (PES ;Furhauser et al, 2005), which only assesses the soft tissues, was used in two studies (Erhan Comlekoglu et al, 2018;Schepke et al, 2017), demonstrating improvement in these scores after 1 year in one study (Schepke et al, 2017), while in the other the results were opposite, as they reported slight worsening 8 months after loading (Erhan Comlekoglu et al, 2018).…”
Section: Aesthetic Indicesmentioning
confidence: 99%
“…In the six remaining studies, one used gold (Gallucci, Grutter, Chuang, & Belser, 2011), one zirconia (Thoma et al, 2016) and one alumina (Chen, Nang, Wang, & Luo, 2008) as control abutments, two compared different fabrication methods of ceramic abutments (Schepke, Meijer, Kerdijk, Raghoebar, & Cune, 2017;Wittneben et al, 2017), and one compared two different impression protocols for ceramic abutments (Erhan Comlekoglu, Nizam, & Comlekoglu, 2018). In these six studies, each arm was considered independent and evaluated together with the selected case series when evaluating the behaviour of the abutment material different from titanium.…”
Section: Description Of Selected Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical importance of the present study is the cellular analysis that we have made to compare two different materials that are already being used as implant abutments in clinical studies. These clinical studies report good results even in the most aesthetic sectors [32,33,34].…”
Section: Discussionmentioning
confidence: 99%
“…4). Okklusale und vestibuläre Ansicht der semipermanent eingegliederten Zirkonoxidkeramikkrone.ses als "One-Abutment-One-Time" bezeichnete Vorgehen scheint biologisch Vorteile zu bieten und das Risiko für einen periimplantären Knochenverlust zu reduzieren[13,14,17]. Es ist jedoch zu berücksichtigen, dass das Anpassen der Restauration an eine sich im Verlaufe desPraxisklinik für Zahnmedizin PD Dr. S. Rinke, Dr. M. Jablonski & H. Ziebolz…”
unclassified